A learning design approach for exploring a framework for mediating collaborative knowledge-building in the Caribbean Educators Network - Hill, LeRoy (2011)
Collaborative knowledge-building (CKB) in online social networking settings is an area of concern among educators and researchers alike. The focus however, seems to be on how social networking sites mediate the process of CKB while neglecting the role of design in making such knowledge-building and collaboration a sustainable activity. The relative lack of attention to design, points to the need for methods to guide the development of CKB environments. Additionally, despite the increasing use and benefits of informal online learning approaches for professional development, many Caribbean educators are still not making effective use of this approach to their professional development. This thesis addresses these issues and contributes to work in the field of learning design in the social networking setting.